2003
DOI: 10.1097/00075197-200311000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceuticals - a pharmaceutical viewpoint: part II

Abstract: Nutraceuticals have potent biological actions. Their use is increasing dramatically, and there is growing evidence of clinical benefits. No medicinal products are completely safe so their risks need to be characterized and controlled. Imposing pharmaceutical levels of control and regulation would increase costs and reduce patient access to new products, but the evidence is compelling that closer monitoring of raw materials, processing and formulation will be required to maximize the benefits and minimize the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Almost 30 years ago, Professors Doll and Peto, after conducting an epidemiological study for the World Health Organization, suggested that appropriate nutrition could prevent approximately 35% of cancer deaths and that up to 90% of certain cancers could be avoided by dietary enhancement [9, 10]. A recent elegant review by Chan and Giovannucci [11] provided an overview of the epidemiological evidence supporting the roles of diet, lifestyle, and medication in reducing the risk of colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Almost 30 years ago, Professors Doll and Peto, after conducting an epidemiological study for the World Health Organization, suggested that appropriate nutrition could prevent approximately 35% of cancer deaths and that up to 90% of certain cancers could be avoided by dietary enhancement [9, 10]. A recent elegant review by Chan and Giovannucci [11] provided an overview of the epidemiological evidence supporting the roles of diet, lifestyle, and medication in reducing the risk of colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Given that complete removal of the causative agents of cancer is most often not possible, effective measures for prevention of cancer is an area currently under active investigation [4]. Nutritional or chemo-prevention of cancers using various antimutagens and/or anticarcinogens present in dietary supplements, especially from food/spice plants has been repeatedly shown to offer various degrees of protection against cancers; and sometimes high efficacy has been shown [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is now believed that 90-95% of all cancers are attributed to lifestyle, with the remaining 5-10% attributed to faulty genes [7]. Almost 30 years ago epidemiological research suggested that appropriate nutrition could prevent approximately 35% of cancer deaths, and up to 90% of certain cancers could be avoided by dietary enhancement [23,24].…”
Section: Nutrition and Colon Cancermentioning
confidence: 99%